Posttraumatic rupture of interventricular septum - O. J. Solodilova; E. V. Viskubova; I. A. Shelestova; K. O. Barbukhatti (Инновационная медицина Кубани)
Cardiac rupture is a extremely acute condition, and it often results in fatality. Main causes of heart rupture are myocardial infarctions, traumas and infections. Recently we have observed increases post-traumatic heart diseases. Timely diagnostics substantially influences management of the patient and potential for survival. And the echocardiography is a reliable, noninvasive and high-informative method in early diagnosis of this pathology. We present a case of the post-traumatic interventricular septum rupture diagnosed by echocardiography and the subsequent xenopericardial patch repair.